2020
DOI: 10.1155/2020/2949125
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Quality of Randomized Controlled Trials for the Treatment of Eczema with Chinese Patent Medicine Based on the CONSORT‐CHM Formulas 2017

Abstract: Objective. Chinese patent medicine (CPM) has been widely used to treat eczema in mainland China for decades. This study aims to investigate circulating CPM for eczema in mainland China and to evaluate the reporting quality of randomized controlled trials (RCTs) of them by using the CONSORT-CHM formulas 2017 (Consolidated Standards of Reporting Trials for Chinese herbal medicine formulas 2017). Methods. Circulating CPM with the indication for eczema was selected by searching three drug databases and confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The documentation about the quality of herbal medicine formulas was poor according to the CONSORT checklist in 2006 ( Bian et al, 2006 ) 4 . In addition, a systematic review ( Li et al, 2020 ) of Chinese patent medicine for eczema showed the mean overall quality score was not good with reference to the CONSORT-CHMF 2017 statement.…”
Section: Discussionmentioning
confidence: 99%
“…The documentation about the quality of herbal medicine formulas was poor according to the CONSORT checklist in 2006 ( Bian et al, 2006 ) 4 . In addition, a systematic review ( Li et al, 2020 ) of Chinese patent medicine for eczema showed the mean overall quality score was not good with reference to the CONSORT-CHMF 2017 statement.…”
Section: Discussionmentioning
confidence: 99%
“…We also conducted multivariate regressions and prespecified subgroup analyses ( Liu et al, 2023b ) to investigate factors that influence the quality of reporting. These factors included: (1) type of journal (integrative and complementary medicine versus non-integrative and complementary medicine journals, definition according to Journal Citation Reports, https://jcr.clarivate.com/jcr/browse-journals ), (2) year of publication (2009 and earlier versus 2010 and later for the CONSORT statement; 2016 and earlier versus 2017 and later for the CHM formula extension), (3) sample size (below median versus above median), (4) number of authors (below median versus above median), (5) multicenter (yes versus no), (6) type 2 diabetes mellitus (T2DM) studied only (yes versus no), (7) TCM patterns studied (yes versus no), and (8) positivity of primary outcome (yes versus no).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent systematic reviews on various conditions, including eczema, essential hypertension, stroke, acute upper respiratory infection in children, prostate cancer, and male infertility, have highlighted the disappointing reporting quality of RCTs involving CHMF (Li et al, 2020;Xu et al, 2020;Tian et al, 2022;Yu et al, 2022;Yan et al, 2023;Zhang et al, 2023). Specific flaws identified include: 1) inadequate reporting on study design (such as the method of randomization), which easily arise a risk of bias that could impact the reliability and validity of the findings (Li et al, 2020;Zhang et al, 2023). 2) a lack of awareness among authors regarding the detail description of CHMF interventions.…”
Section: Introductionmentioning
confidence: 99%